Implementasi Metode Bercerita Dalam Menanamkan Nilai Moral Dan Agama Siswa Di TK Arridho Cengkareng Jakarta Barat - Istiqomah, Siti; Yasin, Nur Septianita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2024)
In modern times today many children still commit deviant acts, acts of violence, behave impolitely and commit actions prohibited in religion. This can happen due to lack of religious and moral cultivation from an early age. Therefore, the author wants to examine the implementation of the storytelling method in instilling students moral and religious values in Arridho Cengkareng Kindergarten, West Jakarta. The purpose of this study is to find out how the implementation of storytelling methods in instilling students' moral and religious values, especially in children aged 4-5 years at Arridho Cengkareng Kindergarten, West Jakarta. This study used a descriptive type qualitative research approach. Primary data sources and secondary data The results of research conducted at Arridho Kindergarten Cengkareng West Jakarta that the implementation of the storytelling method in Arridho Kindergarten has fulfilled three stages, namely 1) planning, 2) implementation, 3) evaluation, Supporting this method is habituation, awareness of participants